Pediatric vs. Adult Prodrome and Postdrome: A Window on Migraine Pathophysiology? - Cuvellier, Jean-Christophe (Frontiers in Neurology, 2019)
Few studies have been conducted on the prodromal and postdromal phases of the migraine attack in children and adolescents. Using a questionnaire, we found that 67% of 103 children and adolescents with migraine reported at least one prodromal symptom, with a mean number per subject of 1.8 (median 2.2). The most frequently reported prodromal symptoms were face changes, fatigue and irritability. In pediatric patients selected as having prodrome, the most frequently reported prodromal symptoms were fatigue, mood change and neck stiffness. Using a different design, Laurell et al. found that 71% of 137 pediatric patients reported at least one prodromal symptom with a mean number per subject of 1.9±2.0. Studying postdrome was fraught with unexpected difficulties as our preliminary research showed. Patients reported 2 groups of symptoms occurring during the resolution phase of the headache: symptoms that had begun before the headache had resolved and were persistent after migraine headache cessation, and symptoms that had begun after the headache had resolved. We referred to the former as persistent symptoms and to the latter as true postdromes. Ninety-one per cent of patients reported persistent symptoms, with a mean of 6.0 and a median of 2, asthenia, pallor, cognitive difficulties, anorexia, somnolence, and nausea being the more frequently reported. True postdromes were reported by 82% of patients, with a mean of 2.6 and a median of 2, thirst, somnolence, visual disturbances, food craving, paraesthesias, and ocular pain being the more frequently reported. Interestingly, several prodromal and postdromal symptoms are also encountered during the aura classic and/or accompany the headache phase. Functional imaging in migraine has showed that the activations in areas such as hypothalamus or brainstem may begin before headache onset and/or persist after headache relief. Thus, one may wonder whether prodromal and postdromal symptoms may indicate the involvement of the limbic system, dopaminergic pathways, the hypothalamus and the brainstem. Differences between children, adolescents and adults might contribute to the understanding of migraine neurobiology.